2021
DOI: 10.18502/fid.v18i10.6134
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Theobromine and Sodium Fluoride Solutions for Remineralization of Initial Enamel Caries Lesions

Abstract: Objectives: This study investigated the efficacy of theobromine in comparison with 0.05% sodium fluoride solution for remineralization of initial enamel caries lesions (IECLs). Materials and Methods: Ninety non-carious extracted premolars were sectioned longitudinally into buccal and lingual segments. Caries-like lesions were induced in each segment using acidified gel.  Forty-five buccal segments were used for surface microhardness (SMH) test, and 45 buccal segments were used for energy-dispersive X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The composition of Theodent is given in table 3. Premanth JP et al [17] and Shawky R et al provided comparable results on theodent toothpaste. Insignificant differences were found between theobromine and fluoride dentifrices [18].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The composition of Theodent is given in table 3. Premanth JP et al [17] and Shawky R et al provided comparable results on theodent toothpaste. Insignificant differences were found between theobromine and fluoride dentifrices [18].…”
Section: Discussionmentioning
confidence: 83%
“…Amaenchi B et al evaluated 1.1mmol/l theobromine concentration [12]. Four studies [13,14,15,16], except two studies on dentifrices [17,18] and one study on novel varnish [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported no signi cant difference following SEM-EDX analysis and stated that theobromine could be used as an alternative remineralising agent [42]. Farhad et al initially investigated the effectiveness of theobromine on the remineralisation of enamel caries lesions by comparing it with 0.05% sodium uoride solution and reported that the remineralisation effect of theobromine was signi cantly higher than sodium uoride [43]. In contrast, Danaswari et al reported that theobromine prevented a decrease in surface microhardness after bleaching application; they determined that theobromine reduces the increasing microhardness values [44].…”
Section: Evaluation Of Microhardnessmentioning
confidence: 99%